Trust and reciprocity in building inter-personal and inter-organizational commitment in small business co-operatives - Pesämaa, O.; Pieper, T. M.; Vinhas da Silva, Rui; Black, W. C.; Hair, Joe F. (Journal of Co-operative Organization and Management, 2013)
Local co-operative networks are autonomous volunteer united entities that perform a number of economic and social functions in order to sustain. Many of these functions are volunteer efforts such as preparing logotypes, shared marketing, joint sales, and building competencies that a member cannot offer independently. A number of theoretical constructs explain co-operative members’ likelihood to overcome the dilemma of having to focus on short-term, immediate survival and at the same time pursue longer-term, shared objectives. Trust and reciprocity are typically present with differing degrees of intensity in co-operative arrangements. Trust is the ability to respond to perceived uncertainties in order to cope with risk while reciprocity is the norm of give and take in exchanges. With these concepts in mind, the objective of this paper is to examine inter-personal and inter-organizational commitment in the context of small business co-operatives, underscoring the roles of trust and reciprocity as precursors to commitment, as well as ultimate guarantors of inter-firm co-operation in a small-business co-operative environment. The proposed theoretical model is tested using structural equation modeling on a sample of small businesses from the tourist industry. The findings provide implications regarding the roles of trust and reciprocity in building inter-firm relational commitment.